Constraints in the implementation of continuing professional teacher development policy in the Western Cape - Johns, L.A.; Sosibo, Z.C. (South African Journal of Higher Education, 2019)
Continuing teacher professional development (CPTD) is regarded as key to teachers gaining essential pedagogical-content knowledge needed for the 21st century. Despite the existence of formal structures for this system in South Africa, policy implementation continues to present challenges. This study investigated constraints in the implementation of CPTD policy. The research question was ‘What factors inhibit the implementation of CPTD policy in Western Cape education districts? The design was a qualitative case study with purposely-selected sample of principals, teachers, and provincial and district officers. Data were collected through semi-structured interviews and triangulated through document analysis. Data analysis involved colour-coding, categorisation and emergent themes. Results revealed that CPTD implementation frustrated teachers, resulting in negative attitudes, low morale and demotivation. Teachers perceived the CPTD as a compliance activity rather than as a tool for growth and development. This conclusion could imply that policymakers need to rethink ways of improving CPTD implementation.